Faktor Yang Mempengaruhi Kedisiplinan Perawat - Arnianti anti (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Discipline is a matter that becomes a benchmark to find out whether the role of a manager or leader as a whole can be implemented properly or not. A discipline is also a form of nurses 'self-control and regular implementation in demonstrating the level of sincerity of nurses' work in a Health center, where nurses who do not comply with the regulations set by the Health center will get sanctions. Therefore this disciplinary action cannot be applied carelessly, so it requires wise consideration. This study aims to determine the discipline of nurses in Maros Barui Health center. This research is quantitative research. The sample in this study amounted to 50 respondents. Samples were taken with a cross-sectional design, using a non-rundem sampling method with criteria determined by researchers. The results of the chi-square test for personality and environmental factors obtained a p-value of 0.827 that Ha was rejected and H0 was accepted. The application of the results of this study can be used as reference material for learning about nurse discipline. his duty.